Neutrophil granulocyte functional status and expression of apoptosis markers in children with type 1 diabetes - Lyudmila Yur'evna Barycheva; Natalya Eduardovna Erdni-Goryaeva; Galina Alekseevna Alexandrovich (Сахарный диабет)
In recent years, polymorphonuclear leukocytes have been proven to play an important role in the development of diabetes mellitus (DM). Neutrophil dysfunction contributes to pancreatic tissue damage as well as an increased susceptibility to infection in type 1 DM (T1DM) patients. Objective. The objective of this study was to investigate the functional activity of neutrophil granulocytes (NGs) in children with T1DM. Materials and Methods. This study involved 25 children aged 7?15 years. To evaluate programmed cell death, the number of NGs expressing apoptosis markers (CD95, CD95L and BCL2) was determined. The functional activity of NGs was determined in terms of phagocytosis and the levels of myeloperoxidase, lysosomal cationic proteins and active oxygen radicals. Results. A reduction in the bactericidal activity of NGs with deficiencies in phagocytosis, secretion of active oxygen radicals and functional reserve was found. An increase in the apoptotic potential of NGs was demonstrated, which was accompanied by an increase in CD95 expression and a decrease in BCL2 expression. An increase in the cytotoxic potential of neutrophils in the form of enhanced levels of myeloperoxidase and lysosomal cationic proteins was revealed. Conclusions. Therefore, an increase in the apoptotic potential of NGs associated with functional and metabolic changes may reflect the active involvement of NGs in the immunopathogenesis of T1DM.